The Phenomenology of Delirium: Presence, Severity, and Relationship between Symptoms. (2nd January 2014) - Boettger, Soenke; Boettger, Susanne; Breitbart, William
Abstract : Objective . To examine the phenomenological characteristics of delirium based on the Memorial Delirium Assessment Scale (MDAS) in order to explore the presence, severity of, and relationship between symptoms. Methods . An analysis of 100 cases of delirium recruited at Memorial Sloan Kettering Cancer Center (MSKCC) was performed. Sociodemographic and medical variables, the Memorial Delirium Assessment Scale (MDAS) subitems, and Karnofsky Performance Status scale (KPS) were analyzed of respect of the phenomenological characteristics and their interrelationship. Results . The most severe and frequent symptoms were recorded in the cognitive domain, psychomotor behavior, sleep-wake cycle, and disturbance of consciousness. Within the cognitive domain, concentration was the most severely affected task. The severity of impairment in most domains increased with delirium severity, whereas perceptual disturbances and delusions were independent of delirium severity. Advanced age and the prevalence of dementia increased with delirium severity in contrast to the functional status which declined. The presence of perceptual disturbances and delusions was independent of cognitive impairment and psychomotor abnormality, however, associated with the disturbances of consciousness and attention. Conclusion . Cognition, in particular concentration, was the most severely affected domain. Advanced age and the prevalence of dementia contributed to more severe delirium. Perceptual disturbances and delusions were independent of delirium severity; however, they were associated with disturbances of consciousness and attention.